The Charisma of Coastal Ecosystems: Addressing the Imbalance - Duarte, Carlos M.; Dennison, William C.; Orth, Robert J. W.; Orth, Robert J.; Carruthers, Tim J. B. (Estuaries and coasts, 2008)
Coastal ecosystems including coral reefs, mangrove forests, seagrass meadows, and salt marshes are being lost at alarming rates, and increased scientific understanding of causes has failed to stem these losses. Coastal habitats receive contrasting research effort, with 60% of all of the published research carried out on coral reefs, compared to 11-14% of the records for each of salt marshes, mangrove forests, and seagrass meadows. In addition, these highly connected and interdependent coastal ecosystems receive widely contrasting media attention that is disproportional to their scientific attention. Seagrass ecosystems receive the least attention in the media (1.3% of the media reports) with greater attention on salt marshes (6.5%), considerably more attention on mangroves (20%), and a dominant focus on coral reefs, which are the subject of three in every four media reports on coastal ecosystems (72.5%). There are approximately tenfold lower reports on seagrass meadows in the media for every scientific paper published (ten), than the 130-150 media reports per scientific paper for mangroves and coral reefs. The lack of public awareness of losses of less charismatic ecosystems results in the continuation of detrimental practices and therefore contributes to continued declines of coastal ecosystems. More effective communication of scientific knowledge about these uncharismatic but ecologically important coastal habitats is required. Effective use of formal (e.g., school curricula, media) and informal (e.g., web) education avenues and an effective partnership between scientists and media communicators are essential to raise public awareness of issues, concerns, and solutions within coastal ecosystems. Only increased public understanding can ultimately inform and motivate effective management of these ecologically important coastal ecosystems.